Dose-Dependent Effect of Intravenous Administration of Human Umbilical Cord-Derived Mesenchymal Stem Cells in Neonatal Stroke Mice - Tanaka, Emi; Ogawa, Yuko; Mukai, Takeo; Sato, Yoshiaki; Hamazaki, Takashi; Nagamura-Inoue, Tokiko; Harada-Shiba, Mariko; Shintaku, Haruo; Tsuji, Masahiro (Frontiers in Neurology, 2018)
Neonatal brain injury induced by stroke causes significant disability, including cerebral palsy, and there is no effective therapy for stroke. Recently, mesenchymal stem cells (MSCs) have emerged as a promising tool for stem cell-based therapies. In this study, we examined the safety and efficacy of intravenously administered human umbilical cord-derived MSCs (UC-MSCs) in neonatal stroke mice. Pups underwent permanent middle cerebral artery occlusion at postnatal day 12 (P12), and low-dose (1×104) or high-dose (1×105) UC-MSCs were administered intravenously 48 hours after the insult (P14). To evaluate the effect of the UC-MSC treatment, neurological behavior and cerebral blood flow were measured, and neuroanatomical analysis was performed at P28. To investigate the mechanisms of intravenously injected UC-MSCs, systemic blood flowmetry, in vivo imaging and human brain-derived neurotrophic factor measurement were performed. Functional disability was significantly improved in the high-dose UC-MSC group compared with the vehicle group, but cerebral blood flow and cerebral hemispheric volume were not restored by UC-MSC therapy. The level of exogenous human brain-derived neurotrophic factor was elevated only in the cerebrospinal fluid of one pup 24 hours after UC-MSC injection, and in vivo imaging revealed that most UC-MSCs were trapped in the lungs and disappeared in a week without migration toward the brain or other organs. We found that systemic blood flow was stable over the ten minutes after cell administration and that there were no differences in mortality among the groups. Immunohistopathological assessment showed that the percent area of Iba1-positive staining in the peri-infarct cortex was significantly reduced with the high-dose UC-MSC treatment compared with the vehicle treatment. These results suggest that intravenous administration of UC-MSCs is safe for a mouse model of neonatal stroke and improves dysfunction after middle cerebral artery occlusion by modulating the microglial reaction in the peri-infarct cortex.